Description Of Social Support And Academic Adaptation In First Year Students At Study Program Ners Stikes Santa Elisabeth Field: Social Support And Academic Adaptation - Elisa Sinaga; Karo, Mestiana; Saragih, Helinida (STIKes Mandala Waluya Kendari, 2024)
Background: Adaptation is part of surviving with a pattern of adjustment to the environment, both for oneself and the environment and for changing environmental conditions according to one's own circumstances. Social support is as verbal and non-verbal information, advice, real help or behavior provided by people who are familiar with the subject in their social environment, or in the form of presence and things that can provide social benefits or influence behavior or recipient behavior. This study aims to determine the description of social support and academic adaptation in first-level students at the Nursing Study Program STIKes Santa Elisabeth Medan 2023. Methods: This study uses descriptive research. The sampling technique in this study uses total sampling with a total sample of 100 respondents. The instrument used is a questionnaire on the variables of social support and academic adaptation. Results: The study found that most of the 72 respondents (72%) received good social support, the academic adaptation of the majority of 61 respondents (61%) obtained sufficient. Grade I students get a source of social support from their family and peers, and academic adaptation for grade I students on campus and their social environment is still in the adequate category. Conclusions: The author suggests that STIKes Santa Elisabeth Medan, especially for students of the Nursing Study Program level I, to increase social support for students and support the adaptation process on campus so that students' academic adaptation becomes better.